Pemanfaatan Tumbuhan dalam Pengobatan Tradisional Bagi Lansia - Riki Syahroni; Emmy Solina; Rahma Syafitri (Social Issues Quarterly, 2023)
The potential of medicinal plants in Kelarik Utara Village, Bunguran Utara District, which are used by the elderly to be used as traditional medicine in healing diseases. The use of plants to be used as traditional medicine carried out by the elderly is a knowledge that is owned and obtained through learning outcomes passed down by parents from previous elderly. So that with the use of traditional medicines by the elderly, these traditional medicines will continue to exist and continue to be preserved from generation to generation. This study used descriptive research with a qualitative approach and this research was conducted in Kelarik Utara Village, Bunguran Utara District. In collecting data, researchers used techniques in the form of observation, interviews, and documentation. Then how to get research informants using purposive sampling technique, after getting informants the results of the interviews were analyzed using Max Weber's theory of social action. The elderly in Kelarik Utara Village make use of plants because there is knowledge that comes from the elderly themselves and the elderly feel the benefits of the traditional medicines they make so that people have more confidence in the traditional medicines made by the elderly. There are patterns of action taken by the elderly in Kelarik Utara Village in the utilization of plants and the existence of public trust in healing diseases using these traditional medicines. Where the action is a traditional action where there is a habit that is done repeatedly. This instrumental rational action is an action where it is important to use plants to be used as traditional medicine. This affective action is an act of using medicinal plants to help people in need. This value rationality type action is an act of the elderly to help people who need traditional medicine.